Characterization of spray drying microencapsulation of almond oil into taro starch spherical aggregates. (March 2019) - Hoyos-Leyva, J.D.; Bello-Perez, L.A.; Agama-Acevedo, J.E.; Alvarez-Ramirez, J.; Jaramillo-Echeverry, L.M.
Abstract: Taro starch spherical aggregates have good potential as wall material for microencapsulation of hydrophobic compounds. This study considered these spherical aggregates for protection of almond oil against oxidative stress. Encapsulation efficiency, microcapsules morphology and physical and chemical stability of the microcapsules were determined. The total encapsulation efficiency (TE) was 56.0 ± 0.6%, while the effective encapsulation efficiency was 37.5 ± 0.5%. The size of the microcapsules was in the range 1.6–31.1 μm, with porous structure that allows the flow of solvents through the intraparticle cavities. It was found that the almond oil was located mostly in the internal cavities of the spherical aggregates. Spray drying induced an increase in the peroxide value of the almond oil at the time of microencapsulation, which in turn enhanced the chemical stability. The maximum physical stability of the microcapsules was found around 8.2 g∙100 g −1 of moisture content for temperatures in the range 25–45 °C of storage. Overall, the results showed that the spherical aggregates provide protection against oxidation reactions to microencapsulated almond oil. Highlights: Taro starch spherical aggregates have potential for microencapsulation of oil. Total encapsulation efficiency of the almond oil was 56%. Almond oil was located mostly in the internal cavities of the spherical aggregates. Microcapsules size was in the range 1.6–31.1 μm.